2016
DOI: 10.3892/ijo.2016.3597
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) and vitamin C impair development of breast cancer tumors in Lp(a)+; Gulo−/− mice

Abstract: Cancer progression is characterized by loss of extracellular matrix (ECM) integrity, which is a precondition for tumor growth and metastasis. In order to elucidate the precise mechanisms of ECM degradation in cancer we used a genetically modified mouse mimicking two distinct human metabolic features associated with carcinogenesis, the lack of endogenous vitamin C synthesis and the production of human Lp(a). Female Lp(a)+; Gulo(−/−) and control wild-type Balb/c mice without these two metabolic features were ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…In a very recent study Lp(a) and vitamin C were found to impair development of breast cancer in a mouse model, transgenic for human Lp(a) and deficient in endogenous vitamin C production [42]. …”
Section: Lp(a) and Malignanciesmentioning
confidence: 99%
“…In a very recent study Lp(a) and vitamin C were found to impair development of breast cancer in a mouse model, transgenic for human Lp(a) and deficient in endogenous vitamin C production [42]. …”
Section: Lp(a) and Malignanciesmentioning
confidence: 99%
“…The heparin and nanoheparin derivatives show their anti-cancer activities by reducing BC cell proliferation and metastasis 55 . Loss of ECM integrity by plasmin facilitates cancer cell spread and plasmin-induced ECM degradation may be controlled by lipoprotein-A (competitive inhibitor of plasminogen) 56 – 58 . Vitamin C seems to be very important curbing tumor growth, and metastasis as ECM integrity requires vitamin C 58 .…”
Section: Introductionmentioning
confidence: 99%
“…Serum Lp(a) levels were found to be inversely proportional to tumor mass. 9 , 13 Furthermore, Lp(a) levels were significantly lower in HCC patients than in the controls. 7 , 14 – 16 Lp(a) may play a crucial role in controlling tumor growth and expansion as a competitive inhibitor of plasmin-induced proteolysis and through its adhesive properties to extracellular matrix components because of its unique structure.…”
Section: Discussionmentioning
confidence: 89%
“…High Lp(a) levels may protect against tumors, which participate in mitigating extracellular matrix damage during cancer progression, in particular by inhibiting proteolytic processes characteristic of all types of cancer cells. 13 , 17 23 All of these factors might suggest that Lp(a), as one of the major moleculars, affects tumor progression through modulating proteolytic processes during extracellular matrix damage. However, the value of serum Lp(a) in monitoring the recurrence and survival of HCC patients has not been investigated.…”
Section: Discussionmentioning
confidence: 99%